(untitled) (Quinto Sol, 2018)
This dossier contains five articles on the current status and meanings of “regional history” in Argentina, this is an expanding field of studies since the mid-eighties, mainly rooted in Argentine provinces rather than metropolitan universities. Regional historians tend to use local scale and micro-historical approach in order to discuss more consolidated historiographical interpretations on national history. The texts concentrate in two main goals: first, to show which were the most important theoretical and methodological debates among regional historians, but also with mainstream historians; second, to update the regional history research agenda attending to the impacts of the “transnational turn”.